2018
DOI: 10.3390/ma11040591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atmospheric Corrosion on the Mechanical Properties of SAE 1020 Structural Steel

Abstract: Resistance to atmospheric corrosion in different environments located in Chile and the corrosion’s effect on the mechanical properties of SAE 1020 steel were studied. Atmospheric corrosivity categories at each station under study were determined. These categories were C2, for Laja; C3 and C4, for the Arica and Antarctic stations, respectively; and the most aggressive, C5 and higher at Quintero. These specific environments significantly influenced the mechanical responses of steel exposed for 36 months. Rupture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…A part of SO 2 adsorbs onto the surface of steel leading to the presence of diffluent FeSO 4 , which is obtained by the chemical reaction between SO 2 , O 2 , and Fe. Furthermore, H 2 SO 4 is obtained by the further oxidation and strong hydrolysis of FeSO 4 , and then H 2 SO 4 reacts with Fe [27,28]. For steel, this whole process keeps recurring due to autocatalysis so that much rust is generated from a molecule of SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A part of SO 2 adsorbs onto the surface of steel leading to the presence of diffluent FeSO 4 , which is obtained by the chemical reaction between SO 2 , O 2 , and Fe. Furthermore, H 2 SO 4 is obtained by the further oxidation and strong hydrolysis of FeSO 4 , and then H 2 SO 4 reacts with Fe [27,28]. For steel, this whole process keeps recurring due to autocatalysis so that much rust is generated from a molecule of SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The degree of metal deterioration and the type of corrosion product that forms on the surface of metals are directly related to the type of atmosphere it is exposed to, climatic factors, and pollutants. [5,6] Thus, any company making use of metal infrastructures exposed to different types of atmosphere-such as in the electrical sector-are aware of the impact of atmospheric corrosion. In a study on the effects of height on corrosion of carbon steel (CS) and galvanized steel in electrical transmission towers under marine environments throughout Chile, Vera et al [7] found greater material deterioration at greater tower heights, partly due to greater wind-induced corrosion-erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial fumes have also been proven to decrease the quality of building materials due to the direct and indirect effects of chemical reactions [5][6][7]. This is observed in the reduction of strength, mass, or aesthetics of metal structures which can further cause a gradual decrease in the mass of the metal material [8][9]. Moreover, thinning of the metal surface caused by corrosion is also the main reason for the premature damage of infrastructures [6,10].…”
Section: ■ Introductionmentioning
confidence: 99%